Analisis Penerapan Sewa Dengan Implementasi PSAK 73 Terhadap Kinerja Keuangan Perusahaan BUMN Sektor Industri Dasar Dan Kimia Yang Terdaftar Di Brusa Efek Indonesia Tahun 2019-2020 - Chalida Nur Rahmadiyani (AKUNTANSI 45, 2023)
This study focuses on analyzing the implementation of leases with PSAK 73 with the aim of comparing the financial performance of the year before implementation and after implementation and existing accounts experience changes in the form of additions or reductions in the application of PSAK 73 on leases. The method used is qualitative using secondary data, using the financial reports of BUMN companies in the basic and chemical industry sectors in 2019-2020. The research results show changes in the company's financial performance after PSAK 73 and there are new accounts in the form of usufructuary assets and lease liabilities. To see changes in performance by applying the calculation of solvency ratios and profitability ratios, for solvency ratios by calculating DAR (Debit to Asset) and DER (Debit to Equity. As well as calculating profitability ratios with ROA (Return to Assets) and ROE (Retrun to Equity). Companies that have small profits and larger total assets indicate that the company is unable to generate stable profits.